What Distinguishes EMAS Participants? An Exploration of Company Characteristics - Roeland Bracke; Tom Verbeke (Fondazione Eni Enrico Mattei (FEEM), 2007)
Empirical research on the characteristics of environmentally responsive companies has focussed almost exclusively on US and Japanese firms. For Europe, which is commonly considered as the greenest of the three major developed economic markets, similar research is lacking. This paper seeks to fill this gap by empirically investigating the business and financial characteristics, stakeholder pressure and public policies distinguishing companies that have implemented the European Eco-Management and Audit System (EMAS) and those that have not using a unique firm-level dataset of European publicly quoted companies. The contribution of this paper is twofold. First of all, the decision to implement EMAS has not been widely analysed. Secondly, we focus on European firms which allows us to assess if and to what extent European firms behave like their US or Japanese counterparts. We find that the EMAS participation decision is positively influenced by the solvency ratio, the share of non-current liabilities and the average labour cost. Also, two measures of company size are positively associated with EMAS participation: both the absolute company size as well as the relative size of a company compared to its sector average. The profit margin on the other hand exerts a negative influence according to our results. We further show that public policy can heavily influence the EMAS participation decision: companies whose headquarters is located in a member state that actively encourages EMAS have a higher probability of participation.
Keywords: L2; 330; EMAS; European Companies; Public Policy; Umweltmanagement; EU-Umweltpolitik; Öko-Audit; Schätzung; EU-Staaten